Please solve the question given in the description

Asked by mac12303190 | 14th Feb, 2010, 10:54: PM

Expert Answer:

(1+ cosA) (1+cosB) (1+cosC) = (1-cos A)(1-cosB)(1-cosC)

Multiplying out sides by RHS, using (a+b)(a-b) = a2-b2

(1+ cosA)2 (1+cosB)2 (1+cosC)2 = (1-cos2 A)(1-cos2B)(1-cos2C)

(1+ cosA)2 (1+cosB)2 (1+cosC)2 = (sin2 A)(sin2B)(sin2C)

Taking square roots,

(1+ cosA) (1+cosB) (1+cosC) = (sinA)(sinB)(sinC) = (1-cos A)(1-cosB)(1-cosC)






Answered by  | 15th Feb, 2010, 05:35: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.